2001
DOI: 10.1111/j.1574-6968.2001.tb10561.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence ofStaphylococcus epidermidison non-transferrin-bound iron for growth

Abstract: The ability of Staphylococcus epidermidis strains to grow in the presence of human transferrin and varying amounts of ferric iron was studied. At initial bacterial densities up to 10(4) cfu ml(-1), none of the three strains grew when transferrin iron saturation was below the full saturation point, whereas the bacteria grew consistently when transferrin was fully iron-saturated and there was non-transferrin-bound iron in the medium. Precultivation of the bacteria under iron-restricted conditions to induce sider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Trivier and Courcol reported that S. aureus could grow in severely iron-limited media containing 0.04 µM Fe whereas other bacteria could not (35). Martinaho et al also found that the growth initiation of S. epidermidis is dependent on the presence of readily-available iron, i.e., non-transferrin-bound-iron (10). According to the results of the present study, S. aureus grew more actively in SSD broths containing FC or HT and utilized iron from transferrin more efficiently than S. epidermidis or S. saprophyticus (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trivier and Courcol reported that S. aureus could grow in severely iron-limited media containing 0.04 µM Fe whereas other bacteria could not (35). Martinaho et al also found that the growth initiation of S. epidermidis is dependent on the presence of readily-available iron, i.e., non-transferrin-bound-iron (10). According to the results of the present study, S. aureus grew more actively in SSD broths containing FC or HT and utilized iron from transferrin more efficiently than S. epidermidis or S. saprophyticus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo bacterial growth can be stimulated by increased iron-availability, and conversely, bacterial growth can be suppressed by reducing iron-availability. Coagulase-negative staphylococci (CoNS), especially S. epidermidis , are known to be major causative agents of septicemia in patients who have received anticancer chemotherapy or stem cell transplantation, because serum iron levels are elevated in these patients (8-10). Recently, it was reported that S. epidermidis infections in such patients can be prevented by administering human apotransferrin, which is a major iron-withholding protein (11).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the growth of S. epidermidis was inhibited in the presence of the chelator and the inhibitory effect was removed when iron was introduced (35). Anyway, S. epidermidis exhibits a better growth in the patients with increased blood iron (36), and therefore this finding could not be considered surprising. On the other hand, S. epidermidis could be susceptible to the chelator and gene variations probably have not yet been developed to give this property to S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacterial development is strongly dependent on the presence of iron, as evidenced by their highly orchestrated mechanisms of acquiring iron, including heme uptake systems and secretion of siderophores to bind excess ferric iron [ 27 ]. High TSAT and the presence of plasma NTBI are associated with enhanced growth of siderophilic bacteria [ 28 30 ]. Iron availability is thus at the heart of the battle between infectious pathogens and host defenses [ 31 ].…”
Section: Iron: a Double-edged Swordmentioning
confidence: 99%